2016
DOI: 10.1194/jlr.m066530
|View full text |Cite
|
Sign up to set email alerts
|

Major role of adipocyte prostaglandin E2 in lipolysis-induced macrophage recruitment

Abstract: Supplementary key words adipose tissue • cyclooxygenase • eicosanoids • extracellular signal-regulated kinase • fatty acid • infl ammation • lipaseAdipose tissue is the major repository of excess energy stored in the form of triacylglycerol (TAG). During energy need, adipocyte lipolysis involving the hydrolysis of TAG releases FFAs for energy production by different tissues ( 1, 2 ). Adipose tissue also secretes various adipokines, which infl uence energy homeostasis and insulin sensitivity of distant tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 43 publications
(39 reference statements)
1
52
0
1
Order By: Relevance
“…21 Accordingly, in preclinical models, antagonism of COX-2 or genetic inhibition of the prostaglandin E2 pathway improves NASH and resolves fibrosis. 22,23 Collectively these data, together with our current findings, support a potential role for aspirin in the prevention of liver fibrogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…21 Accordingly, in preclinical models, antagonism of COX-2 or genetic inhibition of the prostaglandin E2 pathway improves NASH and resolves fibrosis. 22,23 Collectively these data, together with our current findings, support a potential role for aspirin in the prevention of liver fibrogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…For example, adipocyte-specific Mcp-1 transgenic mice exhibit increased ATMs and whole-body insulin resistance (42). It has been demonstrated that several lipid metabolites released from adipocytes or adipose tissue participate in inflammatory cell activation (15,16,32,43,44). Eicosanoids produced from adipocytes promote recruitment of immune cells (16,32), whereas palmitoleate and palmitic acid-9-hydroxy stearic acid from adipose tissue reduce pro-inflammatory response in immune cells (15,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Certain lipid metabolites, including leukotriene B 4 , PGD 2 , and PGE 2 , promote monocyte/macrophage migration (18,32). To identify potential secreted mediator(s) that can potentiate monocyte migration in adipose tissue of Plin1 Ϫ/Ϫ mice, CM of adipocytes was subjected to lipidomic analysis by nontargeted LC-MS/MS (Table S1).…”
Section: Elevated Prostaglandins Secreted From Plin1 ؊/؊ Adipocytes Pmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 2 is a potent lipid mediator secreted by various cell types in visceral adipose tissue and it appears to be implicated in the regulation of inflammation and adipocytes functions [30]. Different studies have noted that the excess accumulation of visceral fat depends on depot-specific expression of key enzymes involved in adipose tissue functions, including PGE 2 biosynthesis-related enzymes [31]. PGE 2 is the principal prostaglandin produced by visceral adipose tissue including EAT deposit [27], which regulates energy metabolism and, particularly in obesity, contributes to fat-inflammation and obesity-related insulin resistance, through the activation of prostaglandin-endoperoxide synthase 2 (PTGES-2) [32], known also as cyclooxygenase 2.…”
Section: Introductionmentioning
confidence: 99%